Climate change and tourism in Tuscany, Italy: What if heat becomes unbearable? - Mattia Cai; Roberto Ferrise; Marco Moriondo; Paulo A. L. D. Nunes; Marco Bindi (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper investigates the empirical magnitude of climate conditions on tourist flows in Tuscany, exploring the use of a fine spatial scale analysis. In fact, we explore the use of an 8-year panel dataset of Tuscany's 254 municipalities, examining how tourist inflows respond to variation in local weather conditions. In particular, as the area enjoys a fairly mild Mediterranean climate, our analysis focused on temperature extremes at key times of the tourist season, i.e., on maximum summer temperature and minimum winter temperature. Separate analyses are conducted for domestic and international tourists, so as to test the differences in the preferences among these distinct groups (or types of demand). Estimation results show the impact of climate change on tourist flows appears to vary significantly among destinations depending on the kind of attractions they offer, and those areas that host the main artistic and historical sights, affecting predominantly the domestic rather than the international tourists.
Keywords: C23; D01; L83; 330; Domestic Tourists; International Tourists; Municipalities; Maximum and Minimum Daily Temperature; Dynamic Model; Temperature Demand Elasticity; GMM